Seeing and being seen: Co-situation and impression formation using Grindr, a location-aware gay dating app. (August 2015) - Blackwell, Courtney; Birnholtz, Jeremy; Abbott, Charles
While online spaces and communities were once seen to transcend geography, the ubiquity of location-aware mobile devices means that today's online interactions are deeply intertwined with offline places and relationships. Systems such as online dating applications for meeting nearby others provide novel social opportunities, but can also complicate interaction by aggregating or "co-situating" diverse sets of individuals. Often this aggregation occurs across traditional spatial or community boundaries that serve as cues for self-presentation and impression formation. This paper explores these issues through an interview study of Grindr users. Grindr is a location-aware real-time dating application for men who have sex with men. We argue that co-situation affects how and whether Grindr users and their behavior are visible to others, collapses or erases contextual cues about normative behavior, and introduces tensions in users' self-presentation in terms of their identifiability and the cues their profile contains relative to their behavior.